2020
DOI: 10.1101/2020.10.02.324087
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Generative Approach toward Precision Antimicrobial Peptide Design

Abstract: Antimicrobial peptides (AMPs) are peptides with promising applications for healthcare, veterinary, and agriculture industries. Despite prior success in AMP design using physics- or knowledge-based approaches, there is still a critical need to create new methodologies to design peptides with a low false positive rate and high AMP activity and selectivity. Toward this goal, we invented a cost-effective approach which utilizes a generative model to produce AMP-like sequences and molecular simulations to select pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…Furthermore, little validation was done to ensure that AMPGAN v2 is responsive to manipulations of the target microbe and target mechanism conditioning elements, or that the generated sequences feature those attributes. A previous version of AMPGAN v2 was able to generate novel AMPs, 1 but that still leaves the target microbe and target mechanism conditioning elements fairly untested.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, little validation was done to ensure that AMPGAN v2 is responsive to manipulations of the target microbe and target mechanism conditioning elements, or that the generated sequences feature those attributes. A previous version of AMPGAN v2 was able to generate novel AMPs, 1 but that still leaves the target microbe and target mechanism conditioning elements fairly untested.…”
Section: Resultsmentioning
confidence: 99%
“…AMPGAN v2 builds on our previous experience with AMPGAN v1, 54 though there are several differences in the implementation and evaluation procedure that make direct comparison of the two difficult. Full implementation details for AMPGAN v2 can be found in our GitLab repository.…”
Section: Ampgan V2 Design and Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Through experimental validation, the authors further showed that PepGAN was able to generate an AMP twice as strong as the conventional antibiotic ampicillin. In addition, AMPGAN 39 and the follow-up model AMPGAN v2 40 adopted a bidirectional CGAN framework to generate peptides with desired targets, mechanisms, and minimum inhibitory concentration (MIC) values. By introducing an encoder neural network to map peptide sequence to latent representations, the learnt latent space can be more structural and consequently leads to improved data modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we provided a proof of concept for such an application with AMPGAN and tested its ability to design antibacterial peptides. 54 For 12 generated peptides that are cationic and likely helical, we assessed the membrane-binding propensity via extensive molecular simulations. The top six peptides were promoted for synthesis, chemical characterizations, and antibacterial assays.…”
Section: ■ Introductionmentioning
confidence: 99%